Effects of particle sizes, wood to cement ratio and chemical additives on the properties of sesendok (Endospermum Diadenum) cement-bonded particleboard / Jamaludin Kasim ... [et al.] - Kasim, Jamaludin (Research Management Institute (RMI), 2010)
An experimental investigation was performed to evaluate the properties of cement-bonded particleboard made from Sesendok wood. The target board density was set at a standard 1200 kg m". The effect offarticle size, wood to cement ratio and the addition ofsodium silicate and aluminium silicate on the wood cement board properties has been evaluated. A change ofparticle size from 1.0 mm to 2.0 mm has a significant effect on the mechanical properties, however the physical properties deteriorate. Increasing the wood to cement ratio from 1:2.25 to 1:3 decreases the modulus ofrupture (MOR) by 11% and the addition ofsodium silicate improves valuesfurther by about 28% compared to the addition ofaluminum silicate. The modulus ofelasticity (MOE) in general increases with increasing cement content, but is not significantly affected by the addition ofsodium silicate or aluminium silicate, although the addition of their mixture (sodium silicate andaluminium silicate) consistentlyyields greater MOE values. Water absorption and thickness swelling is significantly affected by the inclusion ofadditives and better values are attained using higher wood to cement ratios.